2008
DOI: 10.1093/jn/138.9.1615
|View full text |Cite
|
Sign up to set email alerts
|

Daily Quercetin Supplementation Dose-Dependently Increases Plasma Quercetin Concentrations in Healthy Humans

Abstract: Our aim was to investigate the effects of an oral supplementation of quercetin at 3 different doses on plasma concentrations of quercetin, parameters of oxidant/antioxidant status, inflammation, and metabolism. To this end, 35 healthy volunteers were randomly assigned to take 50, 100, or 150 mg/d (group Q50-Q150) quercetin for 2 wk. Fasting blood samples were collected at the beginning and end of the supplementation period. Compared with baseline, quercetin supplementation significantly increased plasma concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

32
235
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 292 publications
(273 citation statements)
references
References 50 publications
32
235
6
Order By: Relevance
“…This finding is in accordance with our previous human kinetic study (15) and has also been found in pigs (27,28) . However, in contrast to mice and rats, in which nearly one-half of the absorbed amount of quercetin is methylated to isorhamnetin (29 -32) , the proportion of the methylated derivatives in human and pig plasma is rather low (approximately 15 -20 % of total plasma flavonols).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This finding is in accordance with our previous human kinetic study (15) and has also been found in pigs (27,28) . However, in contrast to mice and rats, in which nearly one-half of the absorbed amount of quercetin is methylated to isorhamnetin (29 -32) , the proportion of the methylated derivatives in human and pig plasma is rather low (approximately 15 -20 % of total plasma flavonols).…”
Section: Discussionsupporting
confidence: 94%
“…The plasma profiles of quercetin after the ingestion of 130 mg quercetin from capsules were similar to our previous human study that investigated the kinetics of plasma quercetin from three different quercetin dosages (50, 100 and 150 mg quercetin dihydrate) (15) . In accordance with previous human studies, we observed a relatively high inter-individual variance in plasma concentration -time curves of quercetin, isorhamnetin and tamarixetin following supplementation with quercetin (15 -18) , although our non-smoking female study population was very homogenous with respect to age, baseline plasma quercetin concentrations, body weight, BMI, fat mass and fat-free mass as well as lifestyle and physical activity.…”
Section: Discussionsupporting
confidence: 84%
“…In separate studies, no differences in body mass were detected after supplementation with quercetin in rats fed either high-fat or high-fat-high-sucrose chow (Barrenetxe et al 2006;Yamamoto and Oue 2006). Similar to our findings, Egert et al (2008) showed that low doses of quercetin supplements (50, 100, and 150 mg·day -1 ) for 2 weeks did not alter body mass or percent body fat in healthy human subjects. In addition, in a subset of subjects, quercetin failed to alter resting energy expenditure (Egert et al 2008).…”
Section: Discussionsupporting
confidence: 89%
“…The obesity pandemic has accelerated cell, animal, and human research on the anti-obesity effects of flavonoids (Borchardt and Huber 1975;Melzig 1996;Hase et al 2001;Nagao et al 2001Nagao et al , 2005Nagao et al , 2007Singh et al 2003;Alexander 2006;Greenberg et al 2006;Harwood et al 2007;Bose et al 2008;Egert et al 2008;Ito et al 2008;Stewart et al 2008;Liu et al 2009;Faria et al 2010;Grove and Lambert 2010;Zhu et al 2010). For example, several animal studies indicate that 3-15 weeks of supplementation with green tea extract and epigallocatechin gallate (EGCG) reduce body mass and fat mass (Bose et al 2008;Ito et al 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation